2016
DOI: 10.1055/s-0042-108645
|View full text |Cite
|
Sign up to set email alerts
|

Was berichten Hausärzte und Zahnärzte über ihre Zusammenarbeit? Ergebnisse aus einer qualitativen Exploration

Abstract: Separation by statute determines the cooperation. Oral cavity in daily care is demarcated. Holistic patient care is hindered by a lack of knowledge and daily routines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Generally, there is little connection between general practitioners (GPs) and dentists in primary care. 91 , 92 In a qualitative study of GPs’ and dentists’ experiences and expectations of inter-professional collaboration in Germany, both groups of professionals reported perceived knowledge deficits regarding the other profession. 93 For oral health issues, dentists expected GPs to have basic knowledge and to be able to diagnose halitosis.…”
Section: Halitosis: Practical Considerationsmentioning
confidence: 99%
“…Generally, there is little connection between general practitioners (GPs) and dentists in primary care. 91 , 92 In a qualitative study of GPs’ and dentists’ experiences and expectations of inter-professional collaboration in Germany, both groups of professionals reported perceived knowledge deficits regarding the other profession. 93 For oral health issues, dentists expected GPs to have basic knowledge and to be able to diagnose halitosis.…”
Section: Halitosis: Practical Considerationsmentioning
confidence: 99%
“…Accordingly, sufficient knowledge of dentists with regard to systemic diseases and the measures for prevention of complications (e.g. antibiotic prophylaxis) seem mandatory; in contrast, dentists knowledge about these topics and their interdisciplinary collaboration with general physicians is limited [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individual attempts to contact each other by phone are often unsuccessful due to practice structures and heavy workload. 27 These circumstances have received more attention in recent years-both from a dental [27][28][29] and from a general practice perspective. [30][31][32] Göstemeyer et al 33 identified impeding and facilitating factors of oral healthcare (OHC) and dental treatment of older people in need of care.…”
Section: Lack Of Cooperation Between Dentists and General Practitionersmentioning
confidence: 99%
“…There are no reciprocal referral opportunities, even though dentists and GPs need to rely on each other’s information to coordinate their respective treatments. Individual attempts to contact each other by phone are often unsuccessful due to practice structures and heavy workload 27…”
Section: Introductionmentioning
confidence: 99%